PENGENALAN NILAI-NILAI KEARIFAN LOKAL MELALUI KREASI DAN INOVASI KARYA TARI - Sulastuti, Katarina Indah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
In the midst of world civilization, with advances in information and communication technology that are developing rapidly and increasingly sophisticated, it has a significant influence on the threat of the existence of local wisdom values that live in society, which will result in further distance between people and their own culture. Therefore, it is necessary to introduce the values of the local wisdom of the nation's culture to the younger generation. Strategic efforts to maintain the existence of local wisdom values include continuing to echo local wisdom values among the younger generation. The introduction of local wisdom values can be done creatively and innovatively through dance. As an example of the case in the form of an innovative dance model that contains local wisdom values is the Ham Budaya Dance. Innovation and creation are carried out through classical traditional dance forms (dance that lives in the palace), with the development of its elements. The method used is Practice Led Research, which is an artistic research model with steps (1) Observing phenomena to map problems, and collecting the necessary data from the field (2) Developing dance concepts and designs, (3) Collecting Oral data, Libraries, Documents , (4) Exploration, sorting and selecting data: motifs of dance elements originating from classical dance, local wisdom values of national culture which are important to be introduced and/or conveyed to the younger generation (5) Analysis, deciphering data, observing content and meaning, linking and assembling adapted to the design concept of dance innovation with aesthetic considerations. The result of this artistic research is a creative and innovative dance model that represents the local wisdom values of the nation's culture.